ANALISIS KORELASI ANTARA KANDUNGAN FENOL TOTAL DENGAN AKTIVITAS ANTIBAKTERI EKSTRAK DAN FRAKSI Abelmoschus manihot L. TERHADAP Escherichia coli (PHARMACON, 2019)
ABSTRACT This study aims to determine the total phenol content and Minimum Bactericidal Concentration (MBC) and the correlation of antibacterial activity with the total phonel content of the extract and the fraction of Abemoschus manihot L. against Escherichia coli. Gallic acid was used as a comparison standard in measuring the total phenol content using a UV-Vis spectrophotometer. The total phenolic conten of gedi leaf extract and fraction from Southeast Minahasa were ethanol extract 230.23 ± 0.008 µg GAE / g, n-hexane fraction 238.37 ± 0,024 µg GAE / g, ethyl acetade fraction 269.77 ± 0.016 µg GAE / g, and ethanol fraction 221.51 µg GAE / g. The extracts and fractions were tested for antibacterial activity against E. coli  by dilution method using Nutrient Broth (NB) media at concentrations of 1000 µg / mL,500 µg / mL, and 250 µg / mL. MBC test data (Minimum Bactericidal Concentration) were analyzed using Kolmogrov-smirnov, then continued with pearson correlation test. The result of the normality test showed that the extract and the A.manihot fraction had significantly distributed normal vlue (p> 0.05). Analysis Correlation of Pearson of extracts and fraction of A. manihot with antibacterial activity against E.coli showed significant result (p 0,05). Analisis korelasi pearson ekstrak dan fraksi A.manihot dengan aktivitas antibakteri terhadap E.coli  menunjukkan hasil signifikan (p